1996
DOI: 10.1111/1540-5885.1360530
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting New Product Success: Cross‐Country Comparisons

Abstract: Although considerable effort has been devoted to identifying the factors that contribute to new product success and failure, plenty of work remains to be done in this area. For example, many studies of this subject focus on companies in specific parts of the world (in particular, North America, Europe, and Japan). It remains to be seen whether the findings from these studies apply to the new product development (NPD) efforts of companies in other regions, let alone on a global basis. Sanjay Mishra, Dongwook Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 22 publications
9
127
0
Order By: Relevance
“…The measurements utilized in the empirical analyses reviewed can be broken into two frameworks; (a) a macrolevel where the concern is measuring how the characteristics of product innovation is new to the world, the market, or an industry [4,35,37,40,50,64], and (b) a microlevel where product innovativeness is identified as new to the firm or the customer [41]. In the literature included in this comparison, researchers most frequently used both a macro and a microperspective in modeling the construct [2,10,11,12,31,20,21,45].…”
Section: Macro/microperspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The measurements utilized in the empirical analyses reviewed can be broken into two frameworks; (a) a macrolevel where the concern is measuring how the characteristics of product innovation is new to the world, the market, or an industry [4,35,37,40,50,64], and (b) a microlevel where product innovativeness is identified as new to the firm or the customer [41]. In the literature included in this comparison, researchers most frequently used both a macro and a microperspective in modeling the construct [2,10,11,12,31,20,21,45].…”
Section: Macro/microperspectivementioning
confidence: 99%
“…Some products, of course, may require discontinuities in both marketplace and technological factors. Studies reviewed cover all three of these scenarios; marketplace discontinuity [4,33,50,64], technological discontinuity [10,37], and both types of discontinuities [2,11,12,21,31,35,40,41,45].…”
Section: Marketing/technological Discontinuitiesmentioning
confidence: 99%
“…The most common classification is to distinguish between the process steps from idea to market introduction and to differentiate between technical and marketing activities. Both are studied mainly regarding the quality of execution and the proficiency of these activities (e.g., Cooper and Kleinschmidt, 1986;Parry and Song, 1994;Mishra et al, 1996). Organisational issues are covered, as proposed by Cooper, by researching the role of cross-functional teams and leadership.…”
Section: Figure 1 Third-generation Stage-gate Modelmentioning
confidence: 99%
“…The predevelopment activities, in particular, are often positively correlated with success within the studies (e.g., Cooper, 1988;Kotzbauer, 1992;Parry and Song, 1994;Cooper and Kleinschmidt, 1995c;Mishra et al, 1996;Cooper, 1998;Cooper and Kleinschmidt, 2000). Cooper and Kleinschmidt stress the importance of predevelopment steps and call them 'up-front homework'.…”
Section: New Product Successmentioning
confidence: 99%
“…Nesheim (1997) holds that the target market should be large and rapidly expanding, so the venture should consider market size, intensity of competition, revenue (and margins) potential over five years and potential customers. Mishra et al (1996) and found that markets growth and size are often highly positively correlated with new product success. But conversely, Stuart and Abetti (1987) found a strong negative correlation between success in young technological companies and market attractiveness.…”
Section: Marketingmentioning
confidence: 99%